Electroencephalographic Cross-Frequency Coupling as a Sign of Disease Progression in Patients With Mild Cognitive Impairment: A Pilot Study - Musaeus, Christian Sandøe; Nielsen, Malene Schjønning; Musaeus, Jørgen Sandøe; Høgh, Peter (Frontiers in Neuroscience, 2020)
Mild cognitive impairment (MCI) refers to mild objective cognitive deficits and is associated with later development of Alzheimer’s disease (AD). However, not all patients with MCI convert to AD. EEG spectral power has shown promise as a marker of progression but brain oscillations in different frequencies are not isolated entities. Coupling between different frequency bands so called cross frequency coupling (CFC) has been associated with memory function and may further contribute to our understanding of what characterizes patients with MCI who progress to AD. In the current study, we wanted to investigate the changes in gamma/theta CFC in patients with AD, and MCI compared to HC and in patients with pMCI as compared to sMCI. Furthermore, we wanted to investigate the association with cognitive test scores. EEGs were included at baseline for 15 patients with AD, 25 patients with MCI, and 36 older HC and the patients were followed for up to 3 years. To investigate CFC, we calculated modulation index, which has been shown to be less affected by noisy data compared to other techniques. We found that patients with pMCI showed a significantly lower global gamma/theta CFC as compared to sMCI. In addition, global gamma/theta CFC was significantly correlated with Addenbrook Cognitive Examination score (p-value = 0.030, rho = 0.527). Although not significant, patients with AD, and MCI showed a lower gamma/theta CFC as compared to HC. These findings suggest that gamma/theta CFC is important for proper cognitive functioning and a decrease in gamma/theta CFC in patients with MCI may be a sign of progression. Gamma/theta CFC may therefore serve as a progression marker in MCI, but larger studies are needed to validate these findings.